Freezing Out the Mexican Cops: Bullying as Discrimination at the Police Workplace in Mexico City - Fondevila, Gustavo (International Journal of Criminology and Sociology, 2013)
In recent years, bullying problems in public security or defense institutions have been studied. Such problems are associated with high stress situations, a large workload and pressure in hierarchical organisms that base their success on a rigid system of asymmetric power and authoritarian leadership style. The aim of the current study is to investigate (in-depth interviews and ethnographic work) the patterns of the victims’ subjective cultural perception of a particular type of bullying called freezing out in the Mexico City police forces and the victim´s strategies to avoid it, taking into account their ranks within the structure of the police organization. The key research question is the following: How is the bullying experience called “freezing out” culturally perceived by self-identified targets and how do the victims cope with it? In freezing, the superior officer simply leaves his subordinate without specific instructions (it is not isolation). This could manifest itself as a type of informal punishment or as a desire to exclude the individual from the institution´s work production, temporarily or permanently. The present paper is a case study that analyzes the cultural perception of freezing as social discrimination in the Mexican police force.